Spatially associated clump populations in Rosette from CO and dust maps - Veltchev, Todor V.; Ossenkopf-Okada, Volker; Stanchev, Orlin; Schneider, Nicola; Donkov, Sava; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Spatial association of clumps from different tracers turns out to be a valuable tool to determine the physical properties of molecular clouds. It pro
Gesehen am 08.04.2020